A Comparison between Buck-Boost Inverter with and without Buffer Inductor - Purwadi Agus Darwito; Soebagio Soebagio; Mauridhi Hery Purnomo (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2012)
The electric vehicle inverter requires an induction motor drive with a high output of voltage and current to reduce the number of batteries used and in turn reduce the vehicle’s weight. In this paper compared two single Phase BuckBoost Inverter (SPBBI), that is between the SPBBI conventional topology with SPBBI new topology uses a buffer inductor. The results of comparison are expected that the new inverter topology can strengthen the voltage greater than the conventional inverter topology. The inverter’s components of capacitor and inductor were reconfigured. The circuit was simulated for various carrier and signal frequencies with various load. The simulation results of the proposed topology compared with the simulation results of conventional topologies commonly used in a variety of frequency and load values. It is shown that the output voltage and current can be strengthened significantly, with a value of more than five times of the output voltage compared to the conventional inverter. The new inverter topology is useful to be implemented for the electric vehicle.